PERSAINGAN ,TAK BISA DIELAKKAN - Leokadia Retno Adriani (Bina Ekonomi, 2004)
These article take the position that-e company should look two ways: at the individual customers it has chosen and the specific competitors it intends to beat. Seen another way, focusing only on customers through CRM will help ensure that they are well taken care of and their value recognized. But paying attention to competitors will help ensure that the company itself, its employees, shareholders and others who depend on the organization are also well looked after.